Agricultural Green Total Factor Productivity in Shandong Province of China - Peng, Yuanxin; Chen, Zhuo; Lee, Jay (German Journal of Agricultural Economics, 2024)
Sustainable development of agriculture has an important impact on both society and economy. In order to understand the patterns of spatio-temporal variation and the factors influencing agricultural green total factor productivity (AGTFP), this paper used Shandong province of China as a case study. Utilizing the SBM-DEA and Malmquist models, along with panel regression methods, the study analyzes AGTFP based on data from the Shandong Statistical Yearbook (2009-2019). The results showed that: (1) the AGTFP in Shandong province was smaller than the total factor productivity when not considering the undesirable output, and the AGTFP in most regions of Shandong province needed to be improved. (2) The AGTFP of Shandong province showed an annual rising trend, especially in the eastern and northern regions. (3) In addition to the levels of technology and management, the industrialization and level of personal development of farmers is also shown to have impacted on AGTFP. Recommendations include adopting advanced technologies, enhancing land management, promoting tertiary sector development, expanding agricultural processing, and improving farmer skills through education and training to boost AGTFP to achieve a sustainable agricultural economy.